THE DIGITAL MARKETING COMMUNICATION TOOLS ANALYSIS (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
This paper conducts an analysis of digital marketing communication tools, exploring the diverse array of platforms and strategies employed by businesses to engage with their target audiences in the digital landscape. The study delves into the evolving dynamics of digital marketing, investigating the role of tools such as social media, email marketing, search engine optimization (SEO), and content marketing.